Numerical Analysis of a Plunging NACA0012 Airfoil - Camacho, Emanuel António Rodrigues (2020)
Natural flight has always been the source of imagination for the Human being, but reproducing the propulsive systems used by animals is indeed complex. New challenges in today’s society have made biomimetics gain a lot of momentum because of the high performance and versatility these systems possess when subjected to the low Reynolds numbers effects. The present dissertation has as main objective the study of the influence of the number of Reynolds, angle of attack, frequency and amplitude of the movement in the aerodynamic performance of an airfoil NACA0012 that, vertically moves without any variation of the angle of attack over time. [...]